The Utilization of Native Freshwater Mussel Pilsbryoconcha exilis as Biocontrol of Pathogenic Bacteria Aeromonas hydrophila in Tilapia Aquaculture - Rahman Rahman; Filibertus Tantio; Munti Yuhana; Amalia Putri Firdausi; Ranta Sumadi; Adna Sumadikarta (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2019)
This research aims to evaluate the capacity of freshwater mussel Pilsbryoconcha exilis as a biocontrol agent to prevent the transmission of Aeromonas hydrophila in tilapia cultivation. Briefly, 10 tilapia fish with average bodyweight 7,88±0,25 g were subjected to four treatments in the 8-liter aquarium with three replications in a randomized design trial. The treatments were M1 (one mussel for a two-liter of water), M2 (two mussels for a two-liter of water), and two control treatments without mussel ( M+ and M-). All treatments, except the M-, then challenged by adding A. hydrophila live culture to obtain a final density of 105 CFU mL-1 into the aquarium for 7 days duration. The final survival rate of fish, the water-total bacterial count, and the blood profile of animals were assessed. The research revealed that there is a significant impact from the presence of freshwater mussel on tilapia cultivation. Generally, the M2 treatment showed better results with a significant different (P<0,05) according to the survival rate of fish (100±0,00%), water-total bacterial count (4,53±0,03 log CFU mL-1), and fish leucocytes (4,30±0,70x104 cell mm-3). Nonetheless, there was no different (P>0,05) effect on fish erythrocytes among the treatments. Therefore, the feeding activity of freshwater mussel in the water column able to deplete pathogenic bacteria abundance and prevent pathogen transmission along with increasing the survival rate of fish.